Role of three bird species in the life cycle of two Sarcocystis spp. (Apicomplexa, Sarcocystidae) in the Czech Republic - Máca, Ondřej; González-Solís, David (International journal for parasitology. Parasites and wildlife, 2022)
Birds are one of the groups involved in the development of Sarcocystis Lankester (1882), serving either as intermediate or definitive hosts. The white-tailed sea eagle Haliaeetus albicilla (Linnaeus, 1758), red kite Milvus milvus (Linnaeus, 1758) (both Accipitriformes) and common starlings Sturnus vulgaris Linnaeus, 1758 (Passeriformes) were examined to elucidate their participation in the development of Sarcocystis, as well as to determine the specific identity of the parasites based on morphological and especially molecular analyses. In 2020-2021, one white-tailed eagle, one red kite and five common starlings were parasitologically examined for the presence of Sarcocystis using flotation centrifugation coprological method and by wet mounts of intestinal mucosa scrapings and/or muscle samples. Positive samples were processed by light microscopy, histologically and followed molecularly at four genetic markers (18S rRNA, 28S rRNA, ITS1 and cox1). The white-tailed eagle harboured oocysts/sporocysts of S. arctica Gjerde et Schulze, 2014 in the intestinal mucosa, while the intestinal mucosa of the red kite and breasts and leg muscles of one common starling were positive to S. halieti Gjerde, Vikøren et Hamnes, 2018. Sequences from eagle shared 99.6-100% identity with each other and S. arctica in the red fox (V. vulpes Linnaeus, 1758) from the Czech Republic. Sequences from the common starling and red kite shared 100% identity with each other and with S. halieti in the great cormorant (P. carbo [Linnaeus, 1758]) from Lithuania and H. albicilla from Norway. The white-tailed sea eagle might act as definitive host of S. arctica, whereas the common starling and red kite represent intermediate and potential definitive hosts, respectively, for S. halieti.
Keywords: Wildlife; Red kite; White-tailed eagle; Bird; Common starling; Sarcocysts